2021
DOI: 10.1002/anie.202101335
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Thermocatalytic Activities by Upshifting the d‐Band Center of Exsolved Co‐Ni‐Fe Ternary Alloy Nanoparticles for the Dry Reforming of Methane

Abstract: Dry reforming of methane (DRM) is a feasible solution to address the reduction of greenhouse gases stipulated by the Paris Climate Agreement, given that it adds value by converting trivial gases, CO2 and CH4, simultaneously into useful syngas. However, the conventional Ni catalyst undergoes deactivation due to carbon coking and particle agglomeration. Here we demonstrate a highly efficient and durable DRM catalyst: exsolved Co‐Ni‐Fe ternary alloy nanoparticles on the layered perovskite PrBaMn1.7Co0.1Ni0.2O5+δ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(58 citation statements)
references
References 40 publications
2
56
0
Order By: Relevance
“…The vast investigated Ni catalysts prepared by impregnation or deposition provide limited control of particle stability under the MDR reaction conditions due to the mobility of Ni species over openstructure carriers. 21,22 Post-particle growth procedures can delay Ni agglomeration by encapsulating the particles in oxide layers (e.g., SiO 2 with thickness >10 nm), 23,24 while alloying or adding promoters may diminish coking, 25,26 Here, we show that Ni particles of around 15 nm, confined and stabilized by a surficial multielement-oxide (MEO) thin…”
Section: ■ Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…The vast investigated Ni catalysts prepared by impregnation or deposition provide limited control of particle stability under the MDR reaction conditions due to the mobility of Ni species over openstructure carriers. 21,22 Post-particle growth procedures can delay Ni agglomeration by encapsulating the particles in oxide layers (e.g., SiO 2 with thickness >10 nm), 23,24 while alloying or adding promoters may diminish coking, 25,26 Here, we show that Ni particles of around 15 nm, confined and stabilized by a surficial multielement-oxide (MEO) thin…”
Section: ■ Introductionmentioning
confidence: 79%
“…Hence, controlling these aspects are the dominant considerations for Ni catalyst design. The vast investigated Ni catalysts prepared by impregnation or deposition provide limited control of particle stability under the MDR reaction conditions due to the mobility of Ni species over open-structure carriers. , Post-particle growth procedures can delay Ni agglomeration by encapsulating the particles in oxide layers (e.g., SiO 2 with thickness >10 nm), , while alloying or adding promoters may diminish coking, , although these intricate methods may compromise activity. Therefore, the configuration design of Ni particles is essential to achieve industrially acceptable MDR activity and stability.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of Pd stabilizes Fe–Ni by the formation of a core–shell thin layer of Fe–Ni–Pd. Joo et al observed that the introduction of Fe to Ni–Co catalysts exsolved from PrBaMn 1.7 Co 0.1 Ni 0.2 O 5+d improved their stability for DRM . The introduction of Co shifted the d-band center of the Co–Ni–Fe nanoparticles to enhance catalytic activity and stability.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that active sites generated by exsolution often provide strong metal-support interactions that limit metal sintering at high reaction temperature. 60,61 Thus, the Co/Al 2 O 3 hollow porous nanospheres have potential applications in Fischer-Tropsch synthesis, 62 propane dehydrogenation 63 The above in situ functionalization method enables the rational design of a large library of mesoporous nanoshell supported nanocatalysts. As a typical example, the flame synthesized Ni/SiO 2 (Ni/F-SiO 2 ) was tested as a catalyst for the dry reforming of methane reaction (Figure 4a), with Ni contents of 2 wt.%, 5 wt.%, 7 wt.%, 10 wt.%, and 15 wt.% (Figure S11).…”
Section: Resultsmentioning
confidence: 99%